Clinicopathological Evaluation of Patients with Hormone Receptor–Positive HER2-Negative Metastatic Breast Cancer Progressing on Endocrine Treatment: A Real-World Retrospective Study from a Regional Cancer Center - Shanthala, S.; Amirtham, Usha; Lokesh, K. N.; Jacob, Linu; Babu, Govinda (South Asian Journal of Cancer, 2023)
Metastatic breast cancer (MBC) is an incurable disease with the primary aim of treatment being the improvement of the patient's quality of life and the delay of disease progression. A substantial proportion of patients with hormone receptor (HR)-positive MBC eventually experience progression despite endocrine treatment. As endocrine resistance remains a significant challenge, we aim to comprehend the intricate relationship between clinicopathological characteristics and the utility of various parameters as predictive markers for hormonal treatment response. This study, conducted at a single center, is ambispective in nature and includes hormone receptor (HR)-positive, human epidermal growth factor 2–negative MBC patients who progressed while on endocrine treatment, selected through purposeful sampling. Nominal data were analyzed in terms of frequency distribution, and continuous variables were represented as median/mean ± standard deviation. Spearman's correlation test and chi-square test were employed to examine variable dependencies. Data comparisons were performed using the independent t-test, one-way analysis of variance, or Mann–Whitney's test. The majority of our study participants (n = 44, 64.70%) presented with de novo metastasis, while the remainder (n = 24, 35.29%) were patients who progressed from early-stage breast cancer to metastasis. The overall mean age of our study population at presentation was 47 ± 11 years. Patients with upfront stage 4 tumors presented at an older age, exhibited grade 2 tumors, had a higher frequency of bone-only metastasis, and experienced longer progression-free survival (PFS) compared to patients who progressed from the early stage to metastasis. Multiple visceral involvements had a significant negative impact on PFS in contrast to cases with single visceral or bone-only involvement. No significant associations with PFS were observed for the Ki-67 index, first-line chemotherapy, or endocrine therapy. The extent of metastasis to various organs emerged as the most influential factor in determining PFS. Consequently, we propose the necessity for larger prospective studies aimed at identifying superior or additional biomarkers.
Keywords: hormone receptor-positive metastatic breast cancer; progression; PFS (progression-free survival)